The Effect of Cartoon Movies on Students’ Vocabulary Mastery (A Quasi-Experimental Study at Seventh-Grade Students of MTsN 5 Kaur, Academic Year 2023/2024) - Subtiara, Sakinah (Yayasan Sembilan Pemuda Indonesia, 2025)
Cartoon movie was an alternative that can be used as a learning media in the teaching and learning process. This study examines the effect of cartoon movies on students’ vocabulary mastery. A quasi-experimental design was used, involving 40 seventh-grade students from MTSN 5 Kaur, divided into an experimental group and a control group. The experimental group was taught using cartoon movies, while the control group received conventional vocabulary instruction. Data were collected through pre-tests and post-tests and analysed using t-test. The results showed a significant improvement in the vocabulary mastery of the experimental group compared to the control group. The use of audiovisual media made learning more engaging, interactive, and enjoyable, leading to better retention and comprehension. It can be attributed to their visual and auditory elements, which provide contextual reinforcement, making word acquisition more intuitive and engaging. Additionally, social strategies, such as peer discussions and cooperative learning, further enhance vocabulary retention by encouraging active participation.